Does financial sector development have a sustainable level of effects on inclusive growth in Sub-Saharan African countries? Evidence from dynamic panel threshold analysis - Olayiwola, Abiodun Sunday (Asian Journal of Economics and Empirical Research, 2023)
This study examines the threshold level of financial sector development on inclusive growth in sub-Saharan Africa (SSA) between 2000 and 2020 with the view to ascertain the level of sustainability in the relationship between financial sector development and inclusive growth in SSA countries. Data extracted from the World Development Indicator (WDI) and International Financial Statistics (IFS) were analysed using dynamic panel threshold (DPT) techniques. Findings revealed that there exists a positive and significant sustainable level of financial sector development of 0.098 (out of a scale of 0-1.0) that can stimulate inclusive growth in SSA. Likewise, findings at the sub-regional level showed that three out of four (Western, Eastern, and Central African sub-region) except the Southern African region, indicated the existence of a threshold level of financial sector development that can effectively impact inclusive growth. Therefore, this study concludes that the relationship between inclusive growth and financial sector development in most SSA countries is nonlinear and conditional on certain macroeconomic policies. It is recommended that policymakers in respective SSA sub-regions and countries implement policies that will promote relevant financial innovations, reforms, and efficiency in financial inclusion in other to promote financial development above the minimum threshold level in SSA countries.